Symbolic Implementation of Preliminary Group Classiffication for Ordinary Differential Equations - K. S. Govinder (Journal of Applied Mathematics)
We apply the method of preliminary group classification to ordinary differential equations of the form y(n)=E(x,y,y',…,y(n-1),fi(x)),  i=0,…,m. We show how this method can be implemented via the popular symmetry analysis package PROGRAM LIE provided that the package is supplemented with a small file. We then apply this method to an extension of the generalised Emden-Fowler equation given by y′′ = ∑i=25fixyi.